Kajian Sains terhadap Keharaman Bangkai sebagai Makanan dan Dampaknya bagi Kesehatan - Agus Fakhruddin; Mohammad Rindu Fajar Islamy; Amalia Putri Salsabila; Nabila Erma; Zaki Fahreza Sururi (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2023)
This study aims to analyze the prohibition of carrion for consumption through a scientific approach. A comprehensive understanding of this is expected to be an important foothold for Muslims to adhere to religious principles. The research method uses qualitative with a literature study approach. Data were collected from various credible sources such as journals, books, books of turats, and others. Data analysis uses the Miles and Huberman framework which consists of three steps; 1) data display, 2) data reduction, and 3) conclusion. The results showed: 1) animals that have become carcasses are not 100% the same as the conditions when they were alive; 2) the phagocytosis process that plays a role in maintaining the leukocyte white blood cell system can stop in dead animals and eventually trigger the acceleration of the development of microbes in the body; 3) Microflora contained in carcasses include Salmonella, Campylobacter Jejuni, Listeria Monocytogenes and Escherichia Coli. These microbes are harmful to human health as they can cause diseases such as diarrhea, dysentery, and other clinical infections such as meningitis.